Effects of Blackcurrant Extract and Partially Hydrolyzed Guar Gum Intake on Gut Dysbiosis in Male University Rugby Players - Hiroto Miura; Machi Oda; Kanako Abe; Hiromi Ikeda; Mami Fujibayashi; Naoko Oda; Tomohiro Segawa; Aya Abe; Natsumi Ueta; Takamitsu Tsukahara; Tomohisa Takagi; Yuji Naito; et al. (Microorganisms, 2025)
Our previous study reported that male university rugby players tended to have a gut with a dysbiotic environment, characterized by abundant pathobiont bacteria and an accumulation of succinate, when compared with age-matched, non-rugby playing healthy males. In the present study, we conducted a randomized, double-blinded, placebo-controlled experiment to evaluate the potential of blackcurrant extract and/or partially hydrolyzed guar gum (PHGG) to improve the gut environment of university rugby players. Participants were supplemented with blackcurrant extract and/or PHGG or a placebo for 4 weeks. Beneficial gut bacteria such as Megasphaera spp. tended to increase (p < 0.10) and Bifidobacterium spp. increased (p < 0.05) with the intake of blackcurrant extract and/or PHGG. A subgroup analysis further indicated that, unlike in those with a eubiotic gut environment, the dietary supplements also increased the number of beneficial gut bacteria such as Phascolarctobacterium spp. (p < 0.10) and Faecalibacterium spp. (p < 0.10) and fecal SCFA concentrations (p < 0.05) in participants with a possible dysbiotic gut environment. However, a synergistic effect between blackcurrant extract and PHGG was not clearly observed. Although further investigation is recommended, it was concluded that blackcurrant extract and PHGG can at least be used as functional materials to improve gut dysbiosis in university rugby players.